2021
DOI: 10.1101/2021.02.01.429263
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bioprinting transgenic plant cells for production of a recombinant biodefense agent

Abstract: Transgenic rice cells (Oryza sativa) producing recombinant butyrylcholinesterase (BChE) as a prophylactic/therapeutic against organophosphate nerve agent poisoning, cocaine toxicity, and neurodegenerative diseases like Alzheimer′s were immobilized in a polyethylene glycol-based hydrogel. The cells were sustained for 14 days in the semi-solid matrix, undergoing a growth phase from days 0-6, a BChE production phase in sugar-free medium from days 6-12, and a growth/recovery phase from days 12-14. Throughout this … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…Varma et al reported 3D bioprinting of transgenic Oryza sativa (rice), which produces recombinant butyrylcholinesterase (BChE) 140 as a prophylactic/therapeutic against organophosphate nerve agent poisoning, cocaine toxicity, and neurodegenerative diseases like Alzheimer’s, and cells were immobilized in a polyethylene glycol-based hydrogel. 141 The cells maintained viability similar to those in suspension cultures. They displayed similar sugar consumption trends for 14 days in the semisolid matrix, undergoing a growth phase from days 0–6, a BChE production phase in a sugar-free medium from days 6–12, and a growth/recovery phase from days 12–14.…”
Section: Innovations In 3d Printing Driving the Future Of Bioengineer...mentioning
confidence: 66%
See 1 more Smart Citation
“…Varma et al reported 3D bioprinting of transgenic Oryza sativa (rice), which produces recombinant butyrylcholinesterase (BChE) 140 as a prophylactic/therapeutic against organophosphate nerve agent poisoning, cocaine toxicity, and neurodegenerative diseases like Alzheimer’s, and cells were immobilized in a polyethylene glycol-based hydrogel. 141 The cells maintained viability similar to those in suspension cultures. They displayed similar sugar consumption trends for 14 days in the semisolid matrix, undergoing a growth phase from days 0–6, a BChE production phase in a sugar-free medium from days 6–12, and a growth/recovery phase from days 12–14.…”
Section: Innovations In 3d Printing Driving the Future Of Bioengineer...mentioning
confidence: 66%
“…Varma et al reported 3D bioprinting of transgenic Oryza sativa (rice), which produces recombinant butyrylcholinesterase (BChE) as a prophylactic/therapeutic against organophosphate nerve agent poisoning, cocaine toxicity, and neurodegenerative diseases like Alzheimer’s, and cells were immobilized in a polyethylene glycol-based hydrogel . The cells maintained viability similar to those in suspension cultures.…”
Section: Innovations In 3d Printing Driving the Future Of Bioengineer...mentioning
confidence: 99%